Statistical methods for research workers - Fisher, Ronald Aylmer (Edinburgh : Oliver and Boyd, 1970)
This edition has been prepared from notes left by Sir Roland Fisher at the time of his death, the two principal changes being an extension of Section 29 and the addition of Section 57.4.
Includes index
Bibliography pp. 340-351
aia 25/09/17
Loans
Keywords: Statistics; Biometry; Statistics- methodology